Epidemiology and genetics of endemic goiter. II. Genetic aspects - Freire Maia, A.; Villalba Freire Maia, D.; Morton, N. E. (My University, 1982)
Complex genetic models and segregation analysis were applied to family data obtained in a hyperendemic goiter area in Brazil. The single locus and Falconer's models did not fit the data. Edward's model showed convergency, but statistical concordance has not been obtained. Although the genetic load model explains statistically the family data, it would be hard to imagine that endemic goiter could be explained by a model where synergism among genetic and environmental factors is not assumed.
Keywords: endemic goiter; endocrine system; environment; epidemiology; etiology; genetic analysis; genetic load; goiter; heredity; inheritance; Brazil; Chromosome Mapping; Environment; Female; Genetics, Population; Goiter, Endemic; Human; Male; Models, Genetic; Support, Non-U.S. Gov't; Support, U.S. Gov't, P.H.S.